Postmenopausal calcium supplementation - Andryskowski, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2006)
In postmenopausal period there comes to rapid loss of bone mass reaching even 5% within a year. Administration of calcium only is not sufficient to prevent rapidly advancing loss of calcium from bones. Proper dietary calcium intake, its supplementation in combination with estrogen – progesterone hormone therapy or an alternative method of bisphosphonians application help to prevent fractions in the course of osteoporosis. To minimize bone mass loss, elderly men and women should take 1200 mg of calcium daily in postmenopausal period. As there is great variety of calcium preparations available in the market, a survey of literature has been made to recognize these compounds. These calcium preparations are single salts: inorganic, organic, mixtures of both and many of them are obtained from natural sources. In order to supply the organism with adequate amount of calcium the following should be known: the content of elemental calcium in the preparation, its solubility in water and the degree of calcium absorption from the alimentary tract. Calcium level in an organism, vitamin D concentration, age, pregnancy and the content of vegetable substances in a diet affect calcium absorption. The per cent of absorbed calcium is inversely proportional to the administered dose. Majority of preparations are better absorbed with meals. Supplements produced from natural material have a definite content of lead in the preparation due to common intoxication with this element. Application of calcium supplementation in menopausal and postmenopausal period is necessary and the preparation should be selected in accordance with individual needs of a patient.